2022
DOI: 10.3389/fchem.2022.889579
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Boosting on In Situ Nitrogen-Doped Graphene Oxide for Efficient Bifunctional ORR/OER Activity

Abstract: In the present work, a highly efficient and excellent electrocatalyst material for bifunctional oxygen reduction/evolution reaction (ORR/OER) was synthesized using the microwave-assisted hydrothermal method. In brief, ultrafine hexagonal cerium oxide (CeO2) nanoparticles were tailored on the layered surface of in situ nitrogen-doped graphene oxide (NGO) sheets. The nanocomposites exhibited a high anodic onset potential of 0.925 V vs. RHE for ORR activity and 1.2 V for OER activity with a very high current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…At present, the method to optimize this problem mainly entails the combination with the conductive carrier, although the lack of conductive carriers is a new problem. Byrappa et al synthesized an efficient and excellent bifunctional oxygen reduction/precipitation reaction (ORR/OER) electrocatalyst material by combining CeO 2 with nitrogen-doped graphene (NGO) via the microwave-assisted hydrothermal coupling technique [ 112 ]. Among them, nitrogen-doped graphene oxide promotes high current conduction and fast electron transfer, while the adequate mass transfer through the built-in channels reduces the external transmission resistance in oxygen electrocatalysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the method to optimize this problem mainly entails the combination with the conductive carrier, although the lack of conductive carriers is a new problem. Byrappa et al synthesized an efficient and excellent bifunctional oxygen reduction/precipitation reaction (ORR/OER) electrocatalyst material by combining CeO 2 with nitrogen-doped graphene (NGO) via the microwave-assisted hydrothermal coupling technique [ 112 ]. Among them, nitrogen-doped graphene oxide promotes high current conduction and fast electron transfer, while the adequate mass transfer through the built-in channels reduces the external transmission resistance in oxygen electrocatalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Even the precious metal Pt- and Ru-based catalysts have unsatisfactory bifunctional catalytic properties. Byrappa et al synthesized an efficient and excellent bifunctional oxygen reduction/precipitation reaction (ORR/OER) electrocatalyst material via the microwave-assisted hydrothermal method [ 112 ]. Microwave-assisted hydrothermal coupling technology provides a higher density of active sites on CeO 2 @NGO composites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tafel slope analysis was performed to evaluate the kinetic mechanism of the electrocatalyst during the OER process [26][27][28][29]. The plot of the Tafel slopes shown in Fig.…”
Section: Physicochemical Characterizations Of the Obtained Compositesmentioning
confidence: 99%
“…It's observed that the overpotential kept increasing for 3.5 h, then remained approximately stable for another 7 h without any observable uctuations. As time increases, the overpotential is increased again for another 5 h until it reached a stable state after 15 h and an overpotential of 160 mV up to 21 h. This indicates the long-term stability and durability performance of CSZ 1000/mC 2% electrocatalyst which con rms the rapid charge transfer, facile gas adsorption and diffusion [26][27][28][29][30][31][32][33][34][35].…”
Section: Physicochemical Characterizations Of the Obtained Compositesmentioning
confidence: 99%
“…N-S and Mn co-doped two-dimensional graphene nanosheets were synthesized by Guan et al 38 and the catalyst showed the OER overpotential as low as 296 mV. Wang et al 39 Recently, research on catalysts with the bifunctional activities of ORRs and OERs has gradually become a hotspot, [40][41][42][43][44] in which Co and Fe-based catalysts have attracted the most attention. Wang et al 45 investigated the effect of the coordination number of N atoms on the performance of Co-doped graphene catalysts.…”
Section: Introductionmentioning
confidence: 99%